Baseline data of a sequential multiple assignment randomized trial (STEP study). Issue 10 (30th January 2022) - Hartmann, Jessica A.; Nelson, Barnaby; Amminger, Günther Paul; Spark, Jessica; Yuen, Hok Pan; Kerr, Melissa J.; Polari, Andrea; Wallis, Nicky; Blasioli, Julie; Dixon, Lisa; Carter, Cameron; Loewy, Rachel; et al.
Abstract: Aim: Research has shown that preventative intervention in individuals at ultra‐high risk of psychosis (UHR) improves symptomatic and functional outcomes. The staged treatment in early psychosis (STEP) trial aims to determine the most effective type, timing and sequence of interventions in the UHR population by sequentially studying the effectiveness of (1) support and problem solving, (2) cognitive‐behavioural case management and (3) antidepressant medication with an embedded fast‐fail option of (4) omega‐3 fatty acids or low‐dose antipsychotic medication. This paper presents the recruitment flow and baseline clinical characteristics of the sample. Methods: STEP is a sequential multiple assignment randomized trial. We present the baseline demographics, clinical characteristics and acceptability and feasibility of this treatment approach as indicated by the flow of participants from first contact up until enrolment into the trial. Recruitment took place between April 2016 and January 2019. Results: Of 1343, help‐seeking young people who were considered for participation, 402 participants were not eligible and 599 declined/disengaged, resulting in a total of 342 participants enrolled in the study. The most common reason for exclusion was an active prescription of antidepressant medication. Eighty‐five percent of the enrolled sample had a non‐psychotic DSM‐5 diagnosis and symptomatic/functional measures showed a moderate level of clinical severity and functional impairment. Discussion: The present study demonstrates the acceptability and participant's general positive appraisal of sequential treatment. It also shows, in line with other trials in UHR individuals, a significant level of psychiatric morbidity and impairment, demonstrating the clear need for care in this group and that treatment is appropriate.